PENERAPAN SISTEM KINERJA BERBASIS E-KINERJA PADA PEMERINTAHAN KOTA BEKASI - Latifah; Fatmawati; Ilham; Abdul Gafur (Politeknik STIA LAN Makassar, 2023)
The use of digital technology in government is aimed at managing and working well in an innovation of web application-based practice called e-performance. Implementing an electronic system is a way to improve employee performance in working on a change. One of the changes implemented by the government of Bekasi City is an e-performance-based assessment system. The research method used is a descriptive qualitative research method with a phenomenological approach with data from journal articles, books, and online news that are considered relevant to the application of the e-performance system to government employees in Bekasi City. This research focuses on the implementation of an e-performance-based assessment system in Bekasi City. The purpose of the study is to assess the performance of employees of the Bekasi City government from the perspective of productivity, which is the comparison of workload between input and output. The results showed that the application of the e-Kinerja system in the Government of Bekasi City could be effectively used to monitor the performance of an employee and can be a part of disciplining employees in carrying out their respective duties as a form of accountability. The application of e-Kinerja can be used also as a way to assess the quality of employees' performance and determine the number of employee’s allowances and additional income.